Glycaemic control in athletes - Lippi, G.; Montagnana, M.; Salvagno, G. L.; Franchini, M.; Guidi, G. C. (International Journal of Sports Medicine, 2008)
Physical activity is essential for weight control, for limiting onset and complications of chronic disorders and for preventing impaired insulin sensitivity. Little is known about the glycaemic adaptations of physically active subjects, especially elite and professional athletes. Thus, we evaluated the glycaemic control in elite and professional cyclists by assessing fasting plasma glucose (FPG) and glycated haemoglobin (HbA1c). The study population consisted of 47 male professional road cyclists, 72 male elite road cyclists and 58 male sedentary blood donors. A significant difference was observed for FPG between sedentary controls (96 ± 8 mg/dL) and either elite (91 ± 8 mg/dL; p < 0.001) or professional cyclists (89 ± 8 mg/dl; p < 0.001). Athletes showed a consistent trend towards higher HbA1c values, reaching statistical significance between sedentary individuals and professional cyclists (5.2 ± 0.3 % versus 5.4 ± 0.2 %; p = 0.017). In multiple linear regression analysis, the intensity of physical exercise is inversely correlated with FPG (r = - 0.320; p < 0.001) and directly correlated with HbA1c (r = 0.190; p = 0.006). These results demonstrate a significant association between intensity of the training regimen and both FPG and HbA1c, highlighting the need for establishing the appropriate critical difference for the measurement of FPG and HbA1c according to the training and exercise workload.